first, lets distribute the equation. 5(n^2+n)-3n(2n^2+4n-2) would become
5n^2 +5n -6n^3 -12n^2 +6n
Now we add the like terms.
-6n^3 - 7n^2 +11n
Answer:
232.5
Step-by-step explanation:
If you take 15.50 and multiply it by 15 you get 232.5 if its wrong my apologies
Get this equation into y=mx+b form.
y-2=-3(x-4)
y-2=-3x+12
y=-3x+12+2
y=-3x+14
Hope this helps!
And just a note, this is provided in point-slope formula, meaning there is a point on the line, (4,2), based on the initial equation.
Answer:
-4
Step-by-step explanation:
The slope of a line given two points is given by
m = (y2-y1)/(x2-x1)
= (-4-8)/(2 - -1)
= (-4-8)/(2+1)
= -12/3
= -4